CONCERNING K-POP: PENGENALAN SINGKAT TENTANG KOREAN WAVE (HALLYU STAR) - Firda Rizka Rachma Wahdani; Ari Abi Aufa (An-Nas, 2021)
K-Pop is an actual phenomenon nowadays. Widely spread throughKorean dramas, pop songs, boy and girl bands, this Korean culture has becomea symbol of today's youth life. Teenagers in Indonesia, even in other parts of theworld, are competing to imitate the lifestyle of Korean artists, emulating theculture and almost making it as their own culture. This article is a libraryresearch. Writings on Korean popular culture serve as the main source of thisresearch. Writings in the form of a book or journal is analyzed in order to get acomplete understanding of the theme under study. Based on the researchconducted, it is concluded that Korean popular culture is a new culture thatadopts American culture. The new culture is then made into the identity of Koreanyouth and then disseminated through various ways, such as dramas, songs, films,and so on. Utilizing digital technology, social media applications and variousother digital platforms, Korean popular culture has finally managed to spreadwidely and become a phenomenon that has caught the world's attention.